Effect of maturation on the bulk optical properties of apple skin and cortex in the 500–1850 nm wavelength range. (December 2017) - Van Beers, Robbe; Aernouts, Ben; Watté, Rodrigo; Schenk, Ann; Nicolaï, Bart; Saeys, Wouter
Abstract: To facilitate the design of new optical measurement systems for biological systems, the knowledge of light propagation properties is essential. Therefore, the bulk optical properties of skin and cortex of three apple cultivars were studied during maturation, in the 500 nm–1850 nm range. A clear absorption signature was observed with absorption peaks which can be related to present anthocyanins, chlorophyll, carotenoids and water. During maturation, the skin absorption at 550 nm increased in the bicolored cultivars ' Braeburn ' and ' Kanzi ', while the absorption at 680 nm decreased in the cortex. Both the bulk scattering coefficient and the anisotropy factor were larger for the skin compared to the cortex tissue. Also during maturation, the skin scattering increased in the two bicolored cultivars, while a general decrease was seen in the apple cortex. Physiological changes during maturation, like cell growth, the formation/degradation of pigments and the formation of a cuticle layer on the skin, may explain the observed evolutions. As a result, using the bulk optical properties, these physiological changes can be monitored and linked to the maturity stage in the orchard, supporting the selective harvest of apples. Highlights: Apple skin had a higher bulk scattering and anisotropy compared to the cortex. In the visible range, a high absorption by the apple skin was seen in all cultivars. Bulk absorption and scattering properties significantly changed during maturation. The scattering anisotropy remained constant during apple maturation.